A temática evolução nos livros didáticos de biologia utilizados pelas escolas públicas de Araras, SP - Bergamini, Marcela Pagoti; Perinotto, Tiago (Universidade Federal de São Carlos, 2013)
The Synthetic Theory of Evolution is considered the unifier among all theories in Biological Sciences. Before its description, the contents were fragmented into the so-called Natural History. In this context, the importance of learning for understanding science as a whole becomes evident. However, it is noted that nowadays, the theme “evolution” present in textbooks is often approached in a minimalist way, which can lead students to erroneous conceptions, whether due to lack or even failures in the transposition of content. Therefore, the work aimed to analyze the content on evolution present in Biology textbooks used in the state public education system in the city of Araras, SP, according to the distribution made by the PNLD (Programa Nacional do Livro Didático). The three textbooks used were evaluated, pointing out content errors and factors that influence erroneous conceptions on the part of students based on didactic transposition and, therefore, proposing improvements to this teaching and learning tool. To this end, a theoretical basis was carried out through bibliographical surveys of scientific articles and academic books that address the topic of evolution and, subsequently, a comparative analysis of textbooks, following the criteria: simplification affecting the content, existence of conceptual errors, presence of fragmented concepts and relationship with everyday life. After this analysis, possible misconceptions and factors that influence the assimilation of the content were discussed, so that proposals for improvements could be suggested, to assist in the assimilation of this content by students and teachers.
The theme of evolution in biology textbooks used by public schools in Araras, SP
Keywords: Teoria Sintética da Evolução; Lamarck; Darwin; PNLD; Transposição didática; Synthetic Theory of Evolution; National Book and Teaching Material Program; Didactic transposition; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO